Serum Calcium, Magnesium and Creactive protein levels in female Metabolic Syndrome patients - Mohammad, Sumaiya; Shumi, Mahfuja Begum; Nurjahan, Fatema; Begum, Shelina (Journal of Bangladesh Society of Physiologist, 2022)
Background: Metabolic syndrome (Mets) is a risk factor for cardiovascular, chronic lung, liver and kidney diseases. Hypercalcaemia, hypomagnesaemia and elevated C-reactive protein (CRP) produce various complications such as cardiac arrythmia, renal stones, atherosclerosis, Diabetes Mellitus, Obesity etc. Some researchers suggested that hypercalcaemia, hypomagnesaemia and elevated CRP occur in Metabolic syndrome patients. Objectives: To measure serum calcium, magnesium and CRP levels in Metabolic syndrome patients. Methods: This cross sectional study was conducted from March 2019 to July 2020 in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University(BSMMU), Shahbag, Dhaka. For this study, 30 female metabolic syndrome patients aged 25 to 45 year, from the Outpatient department of Endocrinology of BSMMU were selected. For comparison, 30 age and gender matched apparently healthy female subjects were control. Serum calcium and magnesium were measured by Colorimetric method and serum CRP was measured by Immunoturbidimetric method. Independent sample‘t’ test was performed for serum calcium and Mann-Whitney U test was performed for serum magnesium and CRP. Results: Mean serum calcium (p £0.05 and median value of serum CRP (p £0.01) were significantly higher, median value of serum magnesium was lower (p>0.05) but not significant in Metabolic syndrome patients than that of control. Conclusion: This study may conclude that elevated serum calcium and CRP levels are associated with metabolic syndrome patients. J Bangladesh Soc Physiol. 2022, June; 17(1): 14-20